Analysis of the spatial and temporal changes in chlorophyll-a concentration in Qiandao Lake and its impact factors - WANG Fei-er; LÜ Huan-chun; CHEN Ying-xu; TIAN Guang-ming; YU Zuo-ming (浙江大学学报. 农业与生命科学版)
The chlorophyll-a and other water quality indexes were investigated once a month from 1999 to 2000. The spatial and temporal changes in chlorophyll-a concentration in Qiandao Lake were analyzed and the impacts of ecological factors on chlorophyll-a were discussed in the paper. The results showed that the seasonal change of chlorophyll-a concentration was not prominent in the centre and in the outflow of the lake. But it was obvious in the riverine zone and lakefront zone which was evidently influenced by human's activities. Moreover, the concentrations of chlorophyll-a were comparatively high in the riverine zone and lakefront zone. Ecological factors, including nitrogen, phosphorus, water temperature, transparency and precipitation, had significant impact on the concentrations of chlorophyll-a directly and indirectly. However, the main factors were different in different regions of Qiandao Lake.